Analysis of rainwater harvesting for toilet and landscaping needs of building B, Nusa Putra University - Badriyyah Maryam Nur; Adistya Novi; Sagita Salsa Dwi; Saputri Utamy Sukmayu; Sari Nita Kurnita; Marifah Sofa Lailatul (BIO Web of Conferences)
The increasing number of students at Nusa Putra University will lead to high water demand. The research objective was to plan the use of rainwater as an alternative source and design a rainwater harvesting tank. A quantitative descriptive method was used for data collection and analysis. With 1671 students 130 daily staff and a garden of 267.82 m2, efficient water management is necessary. Rainfall data from Ciraden Post for the past 10 years was used. The results showed a rainwater tank capacity of 300 m3 with a total rainwater storage of 1144.82 m3. This tank meets 23% of the toilet and garden water needs every month. The tank is designed using red bricks with a size of 15 m long, 5 m wide, and 4 m high. This research highlights the importance of rainwater utilization in addressing water needs in the campus environment.